Effect of small accounting class on learning effectiveness: a study among college students - ALRiyami , Maisa Zayid; ALAnbar , Khadija Yaqoub; Thottoli, Mohammed Muneerali (Journal of Management and Business Education, 2023)
A larger class with more students will have fewer interactions between students and the teacher due to the teacher's inability to reach each student in a limited time. However, in a small class of ten or fewer students, one will have more opportunities to interact with their teacher. In accounting classes, interaction is one of the most essential aspects. Hence this study aims to explore the effect of Small accounting classes (conduct of a Small class and understanding of Small class) and learning effectiveness among College students across Universities in Oman. This study also measures the mediation effect of class size between independent variables (Conduct of small class, understanding of small class) with the dependent variable, learning effectiveness. A quantitative strategy will be used to collect data for this research. The researcher will use partial least squares structural equation modeling (PLS-SEM) software to examine the data. The study finds that the conduct of a small class significantly affects Learning effectiveness where it was P<0. 001, t=4.032. Likewise, understanding small accounting classes significantly affects Learning effectiveness, which was P<0. 01, t=3.232. However, Class size does not mediate the relationship between the conduct of small accounting classes and learning effectiveness. Likewise, Class size does not mediate the relationship between understanding small accounting classes and learning effectiveness.